1993
DOI: 10.1002/1097-0142(19931101)72:9<2746::aid-cncr2820720936>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1 and childhood cancer

Abstract: Background. Patients with neurofibromatosis type 1 (NF1) are prone to develop malignancy, particularly malignant schwannoma and glioma in adults. Methods. To assess the risk for childhood malignancy in NF1, 26,084 patients with cancer younger than 15 years of age registered from 1969 to 1989 in the Japan Children's Cancer Registry were reviewed. The incidence of NF1 in each type of cancer was compared with that in the Japanese population. Results. Fifty‐six children with cancer had NF1 in the national registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1
3

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(92 citation statements)
references
References 27 publications
(1 reference statement)
3
83
1
3
Order By: Relevance
“…This study confirmed the results of the first population-based study on the incidence of various malignant disorders in neurofibromatosis type 1 (NF-1) (Matsui et al, 1993). The importance of population-based studies of rare diseases cannot be overemphasised.…”
supporting
confidence: 82%
“…This study confirmed the results of the first population-based study on the incidence of various malignant disorders in neurofibromatosis type 1 (NF-1) (Matsui et al, 1993). The importance of population-based studies of rare diseases cannot be overemphasised.…”
supporting
confidence: 82%
“…This has been carried out previously by Matsui et al (1993) and Baptiste et al (1989). Although both these studies verified the increased risk of cancer in NF1, there are problems with this type of study in terms of ascertainment bias.…”
Section: Discussionmentioning
confidence: 80%
“…Previous data have indicated overall additional malignancy risks in NF1 of between 5 and 15% (Sorensen et al, 1986;Huson et al, 1988;Baptiste et al, 1989;Matsui et al, 1993;Stiller et al, 1994;Friedman and Birch, 1997;Zoller et al, 1997;Evans et al, 2002), and these figures are commonly used when counselling patients; therefore, a more specific risk based on a larger study population would be useful. In addition, the advent of surveillance techniques for early detection and subsequent treatment of malignancy suggested that a more detailed analysis of the question of malignancy risk in NF1 was needed.…”
mentioning
confidence: 99%
“…Matsui et al [22] reviewed data from 26,084 Japanese children with cancer and found 56 with NF1, 6.45 times the expected number. Tumor types in the NF1-affected children included optic glioma, other CNS glioma, MPNST, rhabdomyosarcoma, and leukemia.…”
Section: Frequency Of Cancer In Nf1mentioning
confidence: 99%
“…Rhabdomyosarcoma [22] and pheochromocytoma [67] are seen with disproportionately high frequency in individuals with NF1. For other tumors, however, the data are less clear, either because the tumors are rare even in those with NF1, or because the tumors are also common in the general population.…”
Section: Other Malignancymentioning
confidence: 99%